Faktor yang Mempengaruhi Perilaku Konsumen Terhadap Keputusan Pembelian Speedy Pada PT. Telekomunikasi Indonesia Site Operation Panakukang Makassar - Lilies Handayani (el-Idarah: Jurnal Manajemen Pendidikan Islam, 2020)
The aims of the study were to: (1) describe the headmaster’s emotional intelligence in SMA Negeri 3 Polewali, Polewali District of Polewali Mandar Regency; (2) describe the teachers’ performance in SMA Negeri 3 Polewali, Polewali District of Polewali Mandar Regency; (3) describe the significant influence of the headmaster’s emotional intelligence on the teachers’ performance in SMA Negeri 3 Polewali, Polewali District of Polewali Mandar Regency; The study was a quantitative research with the ex-post facto type of research i.e. to look for a causal relationship that was not manipulated or treated by the researcher. It was employed the normative-theological, juridical, and psychological approaches. The population was all 56 teachers in SMA Negeri 3 Polewali and 56 people were taken as samples using saturated sample. Analyzed using descriptive and inferential statistical analysis techniques. The results of the study revealed that: (1) the descriptive analysis result of the headmaster’s emotional intelligence in SMA Negeri 3 Polewali was generally in the medium category with a frequency of 19 of 56 teachers or 34%, (2) the descriptive analysis result of the teachers’ performance in SMA Negeri 3 Polewali was generally in the high category with a frequency of 19 of 56 teachers or 34%, (3) the result of inferential analysis was obtained tcount = 6.442 > ttable = 2.7, so Ho was rejected and H1 was accepted meaning that there was a significant influence of the headmaster’s emotional intelligence on the teachers’ performance in SMA Negeri 3 Polewali;